Microbes Responsible For Acute Exacerbation of COPD - Bari, MR; Hiron, MM; Zaman, SM; Rahman, MM; Ganguly, KC (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):576-85 The abstract of this article is available on the PubMed website